BIMINIMAL GENERAL HELIX IN THE HEISENBERG GROUP Heis3 - Turhan, Essin; Korpinar, Talat (Univ Kragujevac, Fac Science, 2010)
In this paper, we study biminimal curves and characterize non-geodesic biminimal general helix in the Heisenberg group Heis(3). We show that non-geodesic biminimal general helix are biharmonic curves. Morover, we obtain the position vectors of biminimal general helix in the Heisenberg group Heis(3).
Keywords: Heisenberg group; Biminimal curve; General helix